Bioassay‐directed fractionation and sub‐fractionation for mutagenicity and chemical analysis of diesel exhaust particles. (16th September 2013) - Mutlu, Esra; Warren, Sarah H.; Matthews, Peggy P.; King, Charly; Linak, William P.; Kooter, Ingeborg M.; Schmid, Judith E.; Ross, Jeffrey A.; Gilmour, M. Ian; DeMarini, David M.
Abstract : Several types of diesel exhaust particles (DEPs) have been used for toxicology studies, including a high‐organic automobile DEP (A‐DEP) from Japan, and a low‐organic forklift DEP developed by the National Institute of Standards and Technology (N‐DEP). However, these DEPs were not characterized extensively for chemical composition or sub‐fractionated and tested extensively for mutagenicity. We collected a compressor‐generated DEP (C‐DEP) and characterized it by conducting bioassay‐directed fractionation of the extractable organics in Salmonella and correlating the results by hierarchical clustering with the concentrations of 32 polycyclic aromatic hydrocarbons (PAHs). Relative to A‐ and N‐DEP, the mutagenic potency of C‐DEP was intermediate in TA100 +S9 (PAH mutagenicity) but was lowest in TA98 –S9 (nitroarene mutagenicity). More than 50% of the mass of the extractable organics of C‐DEP eluted in the nonpolar Fraction 1, and only ∼20% eluted in the moderately polar Fractions 2 and 3. However, most of the mutagenicity eluted in Fractions 2 and 3, similar to A‐DEP but different from N‐DEP. HPLC‐derived mutagrams of 62 sub‐fractions per fraction confirmed that most of the mutagenicity was due to moderately polar compounds. The diagnostic strains identified a strong role for PAHs, nitroarenes, aromatic amines, and oxy‐PAHs in the mutagenicity of C‐DEP. Hierarchical clustering confirmed the importance of oxy‐PAHs but not that of nitroarenes. To our knowledge this is the first use of hierarchical clustering to correlate chemical composition with the mutagenicity of a complex mixture. The chemical analysis and mutagenicity of C‐DEP described here makes C‐DEP suitable for additional toxicological studies. Environ. Mol. Mutagen. 54:719–736, 2013. © 2013 Wiley Periodicals, Inc.